Dinamika Kebijakan Pemerintah Kota Denpasar Terhadap Revitalisasi Pasar Sindu di Desa Sanur - hasibuan, Zulinda Romadhona; Erawan, I Ketut Putra; Noak, Piers Andreas (Jurnal Nawala Politika, 2019)
ABSTRACT Traditional market can not be separated from human being, in order to full fill the form of basic necessity such as Clothes, Foods, and Home because these kind of things can not be formed and producing it goods and service by itself. Thus society can be easily to full fill their necessities by the existence of the market as a place for trading all goods and products has been showed in Sindu market development by economical point of view followed by tourism sector which is carrying Sanur Village into a revolution. The government has committed to revitalize traditional market in Denpasar City and one of the proof of the commitment shown by supporting and authenticatring a program of Sindhu Traditonal market’s revitalization as it agenda. Theory that used in this research are Rational Choice theory and Agenda Setting which utilized by the Qualitative methods by getting an information by deep interview. The result of this research is showing a dinamics of the government in the process of revitalization by authenticating that agenda and as supporting idea which is harmonized for both of sector in this revitalization agenda. Keywords: Sindhu market, Government Support, Traditional Market’s Revitalization.